Ionizing Radiation Effects and Applications - Djezzar, Boualem (IntechOpen, 2018)
The benefits of ionizing radiations have been largely demonstrated through many achievements of human life. Understanding the fundamental elementary interactions of ionizing radiations with material has allowed the development of various applications needed by different industries. This book draws some facets of their applications, such as hardening process for semiconductor devices, biomedical imaging by radiation luminescent quantum dots, hydrogen gas detection by Raman lidar sensor for explosion risk assessment, water and wastewater purification by radiation treatment for environment, doping by the neutron transmutation doping for the semiconductor industry, and polymerization by irradiation, which is useful for industries requiring resistant and protective coating. I wish the chapters of this book can provide some helpful information on ionizing radiation applications.